Appropriate economic space for transnational infrastructural projects: Gateways, multimodal corridors, and special economic zones - Peter J. Rimmer; Howard Dick (Asian Development Bank Institute (ADBI), 2010)
This study addresses three questions that arise in Asia when formulating, financing, implementing, and maintaining transnational linkages versus purely domestic connections. Firstly, how is optimal economic space to be defined as a useful starting point? Secondly, how can relevant criteria be developed to define the emerging spatial economy and identify efficient transnational transport networks? Thirdly, what are the main investment opportunities in physical infrastructure that would result in more efficient and effective regional cooperation and integration (making special reference to the potential role of crossborder special economic zones (SEZs) or their equivalents)?
Keywords: R00; R10; R30; R40; R50; 330; Verkehrsinfrastruktur; Grenzüberschreitender Güterverkehr; Infrastrukturinvestition; Internationale Zusammenarbeit; Wirtschaftssonderzone; Asiatisch-pazifischer Raum